P.105: Normally Black‐Electrically Controlled Birefringence Mode with Patterned Electrode Structure. Issue 1 (1st July 2013) - Yu, Seung Hun; Choi, Yoonseuk; Kwon, Jin Hyuk; Gwag, Jin Seog
Abstract In order to improve low contrast ratio of the conventional ECB mode and gray inversion of twist nematic mode [TN], a normally black ECB mode is presented It is characterized by λ/2 plate and patterned electrode structure as like the electrode structure of PVA electro‐optic mode. Calculated results show the proposed mode can improve drastically the gray inversion and the contrast ratio, compared with the TN mode and normally white ECB mode